The Pattern Of Javanese Student Love Styles And The Socio-Sexual Lifestyles In The Era Of HIV/AIDS - Shaluhiyah, Zahroh (Jurnal Promosi Kesehatan Indonesia, 2009)
Background: Love is recognized as an important aspect of close relationships and as a predictor of stability in premarital relations. Love has been described as an attitude or value, an emotion, an attachment and as a combination of some of these. In order to understand of sexual subculture of young people, we need to explore their lovestyles which refer to how individuals define or approach love as their attitudes regarding love guiding their behaviour towards, and an experience of, those they love.There are six different styles of love, which were characterized as erotic love, ludic love, storgic love, pragmatic love, maniac love and agapic love. Each person could be characterised by more than one love style. The objective of this study is to identify the pattern of Javanese youth love styles and examine the factors influence to their love styles and sexual lifestyles.Method: Participants were 500 undergraduates (265 males and 235 females) in the age18-24 years. They were recruited from 8 universities in three big cities in Central Java (Semarang,Purwokerto and Surakarta) using a quota sampling method. FGDs and indepth interviews were also conducted to explore in more depth and details the case of premarital sexual relationship of heterosexual couples and homosexuals.Results: The pattern of Javanese youth love styles are firstly pragma and storge. It was influenced by religiousity, personality aspects, level of social activity, and attitudes to premarital sex, sexual attitudes, and sexual experiences. The variety of Javanese youth love styles was signified by development of the individual self or self identity.Keyword: love styles, self identity, Javanese, sexual lifestyles.